Linking organic matter chemistry with soil aggregate stability: Insight from 13C NMR spectroscopy. (February 2018) - Sarker, Tushar C.; Incerti, Guido; Spaccini, Riccardo; Piccolo, Alessandro; Mazzoleni, Stefano; Bonanomi, Giuliano
Abstract: Soil aggregation is considered as a crucial process in agro-system sustainability due to the role in soil physical, chemical and biological dynamics. Here we tested the hypothesis that the initial chemical traits of organic matter (OM) may help to explain the variability of soil aggregation dynamics after organic amendment. We characterized ten OM types (alfalfa litter, biochar, cellulose, glucose, green compost, maize litter, manure compost, meat powder, sawdust, and solid digestate) by 13 C-CPMAS NMR and elemental chemical features to investigate the effects of amendment quality on soil aggregation. In a manipulative factorial experiment, dry samples (200 g) of three soil types (S1, S2 and S3) with different texture, high pH (7–9), and similar OM content, were incorporated with 4 g (2% w/w) of dry, 2 mm-grounded OM, incubated in mesocosms for 300 days under controlled temperature (18 ± 2 °C night and 24 ± 2 °C day), and sampled at 4 dates for measuring aggregation index (AI), based on water stability of soil aggregates (WSA). We found that meat powder and alfalfa litter induced a rapid initial increase of AI, exceeding that of the controls by one to two orders of magnitude, likely acting as a C source for microbes. Biochar incorporation in soil barely affected AI, with intermediate effects with other OM types. Considering C bond types corresponding to OM 13 C-CPMAS NMR spectral regions, carbonyl C was only correlated to early AI, possibly due to overlapping signals of amide structures; O -alkyl C and di- O -alkyl C (carbohydrate fraction) were positively associated to AI, indicating a promoting effect on soil structure, while aromatic C fractions showed an opposite pattern, possibly related to aggregate protection by coatings associated to water repellency, or to direct aggregate internal binding. This study demonstrates that OM chemical quality plays an important role in soil aggregation process, with the molecular composition defined by 13 C-CPMAS NMR spectroscopy being more predictive of aggregation dynamics compared to classical elemental features. As such, this study provides a significant novel contribution to clarify the relationships between OM chemistry and soil aggregation. Graphical abstract: Highlights: Meat powder and alfalfa litter induce rapid soil aggregation. Biochar incorporation barely affects soil aggregation dynamics. Organic matter carbon distribution by 13 C NMR explains soil aggregation patterns. Aggregation is positively associated to carbohydrate fractions of soil amendments. High content of aromatic carbons hamper soil aggregation.